Breast carcinoma in a patient with neurofibromatosis type 1 and huge plexiform neurofibroma of the contralateral breast: a case report - Ayla Kouli; Alyaa Alayoubi; Mousa Alali; Maher Saifo (BMC Women's Health)
Abstract Background Neurofibromatosis type 1 (NF1) is a genetic disorder associated with an increased risk of various cancers, including breast cancer. This report presents a case of a patient with NF1 who had a huge plexiform neurofibroma of the right breast and developed invasive carcinoma in the left breast. Case presentation A woman with a known history of NF1, enlarged right breast, and pectus carinatum presented with locally advanced breast cancer of the left breast. The patient underwent four cycles of neoadjuvant chemotherapy with doxorubicin and cyclophosphamide, followed by a left modified radical mastectomy and axillary lymph node dissection. Postoperative pathology showed a complete pathological response. Subsequently, the patient received four cycles of adjuvant paclitaxel followed by endocrine therapy with anastrozole which was replaced by tamoxifen due to bone and muscle pain. At one year follow-up, the patient remains free of disease. The patient was referred to a plastic surgeon for resection of the enlarged right breast. Conclusion It is known that women with NF1 have a higher risk of developing breast cancer, as demonstrated in our case. These patients could benefit from an early start of breast cancer screening, which could lead to an early diagnosis of early-stage tumors and a better prognosis. Additionally, enhanced access to healthcare centers and intensive surveillance could contribute significantly to better outcomes.